Identification and distribution of gene clusters required for synthesis of sphingolipid metabolism inhibitors in diverse species of the filamentous fungus Fusarium - Hye-Seon Kim; Jessica M. Lohmar; Mark Busman; Daren W. Brown; Todd A. Naumann; Hege H. Divon; Silvio Uhlig; Robert H. Proctor (BMC Genomics, 2020)
Abstract Background Sphingolipids are structural components and signaling molecules in eukaryotic membranes, and many organisms produce compounds that inhibit sphingolipid metabolism. Some of the inhibitors are structurally similar to the sphingolipid biosynthetic intermediate sphinganine and are referred to as sphinganine-analog metabolites (SAMs). The mycotoxins fumonisins, which are frequent contaminants in maize, are one family of SAMs. Due to food and feed safety concerns, fumonisin biosynthesis has been investigated extensively, including characterization of the fumonisin biosynthetic gene cluster in the agriculturally important fungi Aspergillus and Fusarium. Production of several other SAMs has also been reported in fungi, but there is almost no information on their biosynthesis. There is also little information on how widely SAM production occurs in fungi or on the extent of structural variation of fungal SAMs. Results Using fumonisin biosynthesis as a model, we predicted that SAM biosynthetic gene clusters in fungi should include a polyketide synthase (PKS), an aminotransferase and a dehydrogenase gene. Surveys of genome sequences identified five putative clusters with this three-gene combination in 92 of 186 Fusarium species examined. Collectively, the putative SAM clusters were distributed widely but discontinuously among the species. We propose that the SAM5 cluster confers production of a previously reported Fusarium SAM, 2-amino-14,16-dimethyloctadecan-3-ol (AOD), based on the occurrence of AOD production only in species with the cluster and on deletion analysis of the SAM5 cluster PKS gene. We also identified SAM clusters in 24 species of other fungal genera, and propose that one of the clusters confers production of sphingofungin, a previously reported Aspergillus SAM. Conclusion Our results provide a genomics approach to identify novel SAM biosynthetic gene clusters in fungi, which should in turn contribute to identification of novel SAMs with applications in medicine and other fields. Information about novel SAMs could also provide insights into the role of SAMs in the ecology of fungi. Such insights have potential to contribute to strategies to reduce fumonisin contamination in crops and to control crop diseases caused by SAM-producing fungi.